Cerebrovascular dynamics in patients with migraine: near-infrared spectroscopy study. - Akin, A; Bilensoy, D; Emir, U; Gülsoy, M; Candansayar, S; Bolay, H (2006)
Migraine is hypothesized to be a neurovascular coupling disorder where the cerebral vascular reactivity is malfunctioning and measuring hemodynamic changes during migraine without causing more disturbance has always been a challenge. Functional near infrared spectroscopy system (fNIRS) is being proposed as an inexpensive, rapid, safe and accurate alternative to fMRI, transcranial doppler sonography (TCD). We have developed NIROXCOPE 201, a novel device for fNIRS which offers 16 source-detector pairs distributed on a probe that is placed on the forehead. Measuring hemodynamic changes during migraine without causing more disturbance has always been a challenge. Using NIROXCOPE 201, we have attempted to investigate the cerebrovascular reactivity of migraine patients to a breath hold task which produces a metabolic perturbation. Six normals and six migraine patients performed four consecutive breath holding task. We calculated the peak and latencies of the initial dip and recovery phases for [Hb], [HbO(2)], [tHb], and [OXY] signals. [Hb], [tHb], and [OXY] ID and R amplitudes of normals are approximately a magnitude higher than migraine patients (P<0.01), while latencies showed no significant differences. Data suggests an altered neurovascular coupling in frontal cortex of migraine patients interictally. The application of NIROXCOPE 201 to patients suffering from other primary headache disorders will reveal diagnostic as well as therapeutic implications of the presented study.